A method for homogenizing a composite cathode slurry, a cathode sheet, and a lithium ion battery

CN122889703APending Publication Date: 2026-10-09QINGDAO GUOXUAN BATTERY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611040705.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-14
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

[0005]基于背景技术存在的技术问题,本发明提出了一种复合正极浆料的匀浆方法、正极片和锂离子电池,利用该匀浆方法有效解决三元材料与磷酸锰铁锂混合分散时因粒径差异导致的团聚、浆料均匀性差及极片内阻高等问题

Benefits of technology

[0046]第二方面,本发明提供一种锂离子电池正极片,是采用上述匀浆方法制备的正极浆料涂覆在集流体上,经烘干、辊压、分切,得到正极片。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122889703A_ABST
    Figure CN122889703A_ABST
Patent Text Reader

Abstract

The application discloses a kind of composite positive electrode slurry's homogenate method, positive plate and lithium ion battery, and the homogenate method specifically includes the following steps: solvent is divided into 2 parts, to obtain first solvent and second solvent;Bonding agent and conductive agent are added to first solvent, stirring, to obtain conductive glue liquid;Conductive glue liquid, ternary material, lithium iron manganese phosphate are respectively divided into 2 parts;First conductive glue liquid, first ternary material, first lithium iron manganese phosphate are mixed, knead, to obtain first kneading material;Second lithium iron manganese phosphate is added to first kneading material, knead, to obtain second kneading material;Second ternary material is added to second kneading material, knead, to obtain third kneading material;Second conductive glue liquid and second solvent are added to third kneading material, stirring, to obtain positive electrode slurry.The application effectively solves the problem that agglomeration, slurry uniformity is poor and the like such as high internal resistance of pole piece when ternary material and lithium iron manganese phosphate are mixed and dispersed due to particle size difference.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of lithium-ion battery cathode preparation technology, and in particular to a homogenization method for composite cathode slurry, cathode sheet, and lithium-ion battery. Background Technology

[0002] The preparation of composite cathodes by combining ternary cathode materials with lithium manganese iron phosphate (LFP) through slurry preparation can simultaneously achieve high energy density and high safety performance in batteries, making it a promising technology route for the power battery field. However, the physical properties of the two types of active materials differ significantly: commercially available ternary cathode materials are mostly micron-sized secondary agglomerated large particles, while LFP, limited by its low conductivity, is designed with submicron or even nano-sized primary crystal grains in mainstream products. During the direct mixing and homogenization process, LFP microparticles are prone to self-agglomeration or adsorption onto the surface of ternary particles, resulting in uneven dispersion and poor stability of the slurry system, which in turn affects the uniformity of electrode coating, the construction of conductive networks, and the electrochemical performance of the battery.

[0003] In existing technologies, methods to improve the dispersibility of the aforementioned two-component slurry mainly include: first, introducing anionic dispersants into the slurry system, which work synergistically with composite conductive agents to inhibit particle agglomeration; second, employing a multi-stage shearing wet process with multiple equipment in relay, relying on mixers, high-speed dispersers, homogenizers, etc., to apply shearing in stages to optimize the overall mixing process. However, for composite systems with significant differences in the physical properties of large ternary particles and fine lithium manganese iron phosphate particles, the above methods have limited effect on improving dispersion, and the multi-equipment series scheme suffers from drawbacks such as a lengthy process flow and high equipment investment and maintenance costs.

[0004] Therefore, there is an urgent need in this field to develop a targeted, simple, and low-cost homogenization method that can effectively solve the dispersion problem of the ternary cathode material and lithium manganese iron phosphate mixed system, and achieve uniform, stable and synergistic dispersion of the two active materials in the slurry. Summary of the Invention

[0005] Based on the technical problems existing in the background technology, the present invention proposes a homogenization method for composite cathode slurry, cathode sheet and lithium-ion battery. The homogenization method effectively solves the problems of agglomeration, poor slurry uniformity and high internal resistance of electrode sheet caused by particle size difference when ternary materials and lithium manganese iron phosphate are mixed and dispersed.

[0006] In a first aspect, the present invention proposes a homogenization method for composite cathode slurry, which employs a semi-dry homogenization process and includes the following steps:

[0007] S1. Divide the solvent into two parts to obtain the first part of solvent and the second part of solvent; add the binder and conductive agent to the first part of solvent, stir and disperse to obtain the conductive adhesive;

[0008] S2. Divide the conductive adhesive, ternary material, and lithium manganese iron phosphate into two portions each; mix the first portion of conductive adhesive, the first portion of ternary material, and the first portion of lithium manganese iron phosphate, knead and disperse to obtain the first kneaded material;

[0009] S3. Add the second part of lithium manganese iron phosphate to the first kneading material, knead and disperse to obtain the second kneading material;

[0010] S4. Add the second part of the ternary material to the second kneaded material, knead and disperse to obtain the third kneaded material;

[0011] S5. Add the second part of conductive adhesive and the second part of solvent to the third kneading material, stir and disperse to obtain the positive electrode slurry.

[0012] This invention is based on a semi-dry homogenization process. By precisely controlling the order of adding active materials in stages, the active materials are added in three stages. First, a portion of the ternary materials and lithium manganese iron phosphate are kneaded and dispersed to initially construct a mixed framework. Then, easily agglomerated small particles of lithium manganese iron phosphate are added for targeted dispersion. Next, the remaining ternary materials are added, and the large particles of the ternary materials are used to optimize the particle size distribution and prevent the small particles from agglomerating again. Finally, adhesives and solvents are added to improve the conductive and binding network and adjust to the target viscosity and solid content. This effectively solves the problems of difficult dispersion and severe agglomeration caused by the difference in particle size between the two materials.

[0013] It should be noted that although the active material ternary material and lithium manganese iron phosphate are added in two separate additions in this invention, this is due to considerations of industrial production costs and economic benefits, as the technical effects of this invention can be stably achieved with only two additions. However, this invention is not limited to this number of additions. Without departing from the core technical concept of this invention, the active material can also be added to the system in three, four, or even more separate additions, and such equivalent separate addition methods all fall within the protection scope of this invention.

[0014] Further, the solvent is selected from one or more of N-methylpyrrolidone, N-ethylpyrrolidone, propylene carbonate, dihydrol-glucanone, and γ-valerol.

[0015] The adhesive is selected from one or more of polyvinylidene fluoride, hydrogenated nitrile butadiene rubber, polyimide, and polyacrylonitrile;

[0016] The conductive agent is selected from one or more of conductive carbon black, acetylene black, carbon nanotubes, and graphene.

[0017] Preferably, the conductive adhesive has a solid content of 6-14% and a viscosity of 1000-3000 mPa·s.

[0018] In this invention, the specific selection of the solvent, binder, and conductive agent is adapted to the semi-dry system and can ensure the electrochemical and mechanical properties of the electrode.

[0019] The conductive adhesive of this invention has a liquid solid content of 6-14%, which can fully wet the fine lithium manganese iron phosphate particles and avoid insufficient adhesive, powder loss or gel agglomeration; the viscosity is 1000-3000 mPa・s, the spreading and adhesion are uniform, it is easy to build a continuous conductive network, and it is suitable for semi-dry homogenization.

[0020] Furthermore, the mass ratio of the ternary material to lithium manganese iron phosphate is 6-9:1-4; the ternary material is an NCM ternary material.

[0021] Furthermore, the NCM ternary material can be one of the ternary materials such as NCM111, NCM523, NCM622, NCM811, and NCM9 series.

[0022] In this invention, by adjusting the ratio of ternary materials to lithium manganese iron phosphate, the high energy density of ternary materials and the high safety and long cycle characteristics of lithium manganese iron phosphate are taken into account, and the electrode impedance and compaction density are balanced.

[0023] Furthermore, the solid content of the first kneaded material is 68-80%;

[0024] Preferably, the positive electrode slurry has a solid content of 60-68%, a viscosity of 5000-8000 mPa·s, and a fineness of ≤15 μm.

[0025] In this invention, the high solid content of the first kneading material can increase the mutual compression and frictional shearing effect between powder particles. With the help of the strong interaction force generated by the dense arrangement of particles, the agglomerates of lithium manganese iron phosphate are broken up, and the adsorption and coating of fine particles on the surface of ternary particles are inhibited, thus constructing a uniformly distributed ternary / lithium manganese iron phosphate mixed framework.

[0026] This invention enables the slurry to have a fineness of ≤15μm, a stable viscosity of 5000-8000mPa·s, and a solid content of 60-68%, thereby reducing electrode resistance and significantly improving battery discharge specific capacity and cycle stability.

[0027] Furthermore, the linear velocity is controlled segmentally during the homogenization process:

[0028] In S1, the dispersion linear velocity is 10-15 m / s, and the temperature is controlled at ≤35℃; preferably, the dispersion time is 2-6 h.

[0029] In S2, the dispersion linear velocity is 6-12 m / s, and the temperature is controlled at ≤40℃; preferably, the kneading and dispersion takes 60-90 min.

[0030] In S3, the dispersion linear velocity is 10-18 m / s, and the temperature is controlled at ≤40℃; preferably, the kneading and dispersion is carried out for 20-40 min.

[0031] In S4, the dispersion linear velocity is 10-18 m / s, and the temperature is controlled at ≤40℃; preferably, the kneading and dispersion is carried out for 20-40 min.

[0032] In S5, the dispersion is first carried out at a medium speed with a dispersion linear velocity of 10-15 m / s, and then dispersed at a high speed with a dispersion linear velocity of 15-25 m / s. The temperature is controlled at ≤40℃, and degassing is carried out under a vacuum of -0.098~-0.095 MPa. Preferably, the medium speed pre-dispersion is carried out for 20-40 min, and the high speed dispersion is carried out for 60-90 min.

[0033] The dispersion linear velocity of S2 is less than that of S3 and S4.

[0034] In this invention, ternary materials and lithium manganese iron phosphate composite cathode slurry are homogenized in stages. By controlling shear force (linear velocity) and temperature, the active material is dispersed stepwise, thereby improving the stability of the slurry and the electrode performance.

[0035] Furthermore, S1-S5 employ a dual planetary slurry mixer for homogenization;

[0036] The dispersion linear velocity of the dual planetary mixing machine is adjustable in the range of 6-25 m / s.

[0037] In this invention, a single or two planetary slurry mixers are used to complete the entire homogenization process, simplifying the process flow, reducing input costs, avoiding the slurry quality fluctuations caused by multiple material transfers across equipment in traditional multi-machine series processes, and resulting in better production stability.

[0038] Furthermore, the first and second portions of solvent account for 30-70% and 70-30% of the total solvent mass, respectively.

[0039] The first and second portions of conductive adhesive account for 40-80% and 20-60% of the total mass of the conductive adhesive, respectively.

[0040] The first and second portions of the ternary material account for 40-60% and 40-60% of the total mass of the ternary material, respectively.

[0041] The first and second portions of lithium manganese iron phosphate account for 40-60% and 40-60% of the total mass of lithium manganese iron phosphate, respectively.

[0042] In this invention, a segmented feeding process is used to first construct a ternary / lithium manganese iron phosphate composite particle framework; then, the easily agglomerated lithium manganese iron phosphate microparticles are specifically dispersed; the particle size distribution of the ternary large particle system is controlled to physically prevent the fine particles from agglomerating again; after being fully dispersed by gradient shearing, a continuous and complete conductive network is built; finally, the system is adjusted to the target viscosity and designed solid content to obtain a bicomponent cathode slurry with uniform dispersion and excellent stability.

[0043] Furthermore, the mass fractions of the active material, conductive agent, and binder are 90-98%, 0.7-5%, and 1.3-5%, respectively.

[0044] The active material includes ternary materials and lithium manganese iron phosphate, with a mass ratio of 6-9:1-4.

[0045] In this invention, by limiting the ratio range of each substance, the dispersion and rheological properties of the two-component slurry can be adapted while ensuring the high energy density of the electrode.

[0046] Secondly, the present invention provides a positive electrode sheet for a lithium-ion battery, which is obtained by coating a positive electrode slurry prepared by the above-mentioned homogenization method onto a current collector, and then drying, rolling and cutting it to obtain the positive electrode sheet.

[0047] Thirdly, the present invention provides a lithium-ion battery comprising the above-described positive electrode sheet.

[0048] Compared with the prior art, the beneficial effects of the present invention are mainly reflected in the following aspects:

[0049] 1. Improved dispersion uniformity: Based on the semi-dry process, through segmented feeding strategy and key parameter control, materials with different physical properties are treated in a targeted manner, effectively suppressing the agglomeration of lithium manganese iron phosphate and the particle segregation and stratification of ternary materials, and the slurry fineness can be controlled within 15μm.

[0050] 2. Good slurry stability: The formed slurry has stable viscosity (5000-8000mPa·s), high solid content (60-68%), is not easy to settle, and is suitable for high-efficiency coating.

[0051] 3. Excellent electrode performance: High electrode uniformity and perfect conductive network improve the battery's electrical performance and cycle life.

[0052] 4. Strong process controllability: The parameters are clear, making it easy to achieve large-scale production, and no special expensive equipment or complex dispersants are required. Attached Figure Description

[0053] Figure 1 This is a process flow diagram of the homogenization method of the present invention;

[0054] Figure 2 The particle size distribution diagram is shown for the positive electrode slurry prepared in Example 1.

[0055] Figure 3 The circuit performance diagram shows the battery prepared using the positive electrode obtained in Example 1 and Comparative Example 1. Detailed Implementation

[0056] The technical solution of the present invention will now be described in detail through specific embodiments.

[0057] The NCM ternary materials used in the following examples are NCM811 (D50=3μm) and lithium manganese iron phosphate LMFP (D50=0.8μm).

[0058] Example 1

[0059] A homogenization method for composite cathode slurry, such as Figure 1 The image shows the semi-dry homogenization process, with the specific steps as follows:

[0060] S1. Preparation of adhesive solution: 700g of PVDF and 9.0kg of NMP are added to a double planetary mixing machine for mixing. Then, 178g of SP and 122g of CNT are added in sequence. The dispersion linear velocity of the double planetary mixing machine is 14m / s. The mixture is stirred at 35℃ for 3h to obtain 10kg of conductive adhesive solution with a solid content of 10%.

[0061] S2. Basic kneading: Take 8 kg of conductive adhesive liquid, add 14.4 kg of NCM811 and 3.6 kg of LMFP to it, control the solid content to 72%, set the dispersion linear velocity of the double planetary mixing machine to 8 m / s, and disperse at 40℃ for 1.5 h.

[0062] S3, LMFP dispersion: Add 3.6 kg of LMFP to the S2 system, increase the dispersion linear velocity of the double planetary mixer to 14 m / s, and disperse at 40℃ for 30 min;

[0063] S4, System Equilibrium: Add 14.4 kg of NCM811 to the S3 system, reduce the dispersion linear velocity of the dual planetary slurry mixer to 12 m / s, and disperse at 40℃ for 30 min;

[0064] S5. Final dispersion: Add the remaining conductive adhesive and 11 kg of NMP to the S4 system, set the dispersion linear velocity of the dual planetary slurry mixer to 12 m / s, and pre-disperse at 40℃ for 30 min; then increase the dispersion linear velocity to 20 m / s, and disperse at 40℃ and vacuum -0.098~-0.095 MPa for 1.5 h to obtain the positive electrode slurry.

[0065] The prepared cathode slurry was characterized by measuring the particle size using a laser particle size analyzer. Figure 2 As shown, the Dmax of the positive electrode slurry is <10μm.

[0066] The positive electrode slurry prepared in Example 1 has a solid content of 65%, a viscosity of 6570 mPa·s, and a fineness of 10 μm.

[0067] Example 2

[0068] A homogenization method for composite cathode slurry employs a semi-dry homogenization process, the specific steps of which are as follows:

[0069] S1. Preparation of adhesive solution: 700g of PVDF and 9.0kg of NMP are added to a double planetary mixing machine for mixing. Then, 178g of SP and 122g of CNT are added in sequence. The dispersion linear velocity of the double planetary mixing machine is 14m / s. The mixture is stirred at 35℃ for 3h to obtain 10kg of conductive adhesive solution with a solid content of 10%.

[0070] S2. Basic kneading: Take 8 kg of conductive adhesive liquid, add 12.6 kg of NCM811 and 5.4 kg of LMFP to it, control the solid content to 72%, set the dispersion linear speed of the double planetary mixing machine to 6 m / s, and disperse at 40℃ for 1.5 h.

[0071] S3, LMFP dispersion: Add 5.4 kg of LMFP to the S2 system, increase the dispersion linear velocity of the double planetary mixer to 18 m / s, and disperse at 40℃ for 30 min;

[0072] S4, System Equilibrium: Add 12.6 kg of NCM811 to the S3 system, reduce the dispersion linear velocity of the dual planetary mixing machine to 10 m / s, and disperse at 40℃ for 30 min.

[0073] S5. Final dispersion: Add the remaining conductive adhesive and 11 kg of NMP to the S4 system, set the dispersion linear velocity of the dual planetary slurry mixer to 15 m / s, and pre-disperse at 40℃ for 30 min; then increase the dispersion linear velocity to 25 m / s, and disperse at 40℃ and vacuum -0.098~-0.095 MPa for 60 min to obtain the positive electrode slurry.

[0074] The positive electrode slurry prepared in Example 2 has a solid content of 65%, a fineness of 10 μm, and a viscosity of 6720 mPa·s.

[0075] Example 3

[0076] A homogenization method for composite cathode slurry employs a semi-dry homogenization process, the specific steps of which are as follows:

[0077] S1. Preparation of adhesive solution: 700g of PVDF and 9.0kg of NMP are added to a double planetary mixing machine for mixing. Then, 178g of SP and 122g of CNT are added in sequence. The dispersion linear velocity of the double planetary mixing machine is 14m / s. The mixture is stirred at 35℃ for 3h to obtain 10kg of conductive adhesive solution with a solid content of 10%.

[0078] S2. Basic kneading: Take 8 kg of conductive adhesive liquid, add 10.8 kg of NCM811 and 7.2 kg of LMFP to it, control the solid content to 72%, set the dispersion linear speed of the double planetary mixing machine to 12 m / s, and disperse at 40℃ for 1.5 h.

[0079] S3, LMFP dispersion: Add 7.2 kg of LMFP to the S2 system, increase the dispersion linear velocity of the double planetary mixer to 15 m / s, and disperse at 40℃ for 30 min;

[0080] S4, System Equilibrium: Add 10.8 kg of NCM811 to the S3 system, and disperse at 40℃ for 30 min with a dispersion linear velocity of 15 m / s using a dual planetary mixer.

[0081] S5. Final dispersion: Add the remaining conductive adhesive and 11 kg of NMP to the S4 system, set the dispersion linear velocity of the dual planetary slurry mixer to 10 m / s, and pre-disperse at 40℃ for 40 min; then increase the dispersion linear velocity to 15 m / s, and disperse at 40℃ and vacuum -0.098~-0.095 MPa for 90 min to obtain the positive electrode slurry.

[0082] The positive electrode slurry prepared in Example 3 has a solid content of 65%, a fineness of 11 μm, and a viscosity of 6960 mPa·s.

[0083] Comparative Example 1 (Conventional single-feed wet process)

[0084] A homogenization method for a composite positive electrode slurry, which differs from Example 1 in that the active material is added and dispersed in a single step, as detailed below:

[0085] S1. Preparation of adhesive solution: 700g of PVDF and 9.0kg of NMP are added to a double planetary mixing machine for mixing. Then, 178g of SP and 122g of CNT are added in sequence. The dispersion linear velocity of the double planetary mixing machine is 14m / s. The mixture is stirred at 35℃ for 3h to obtain 10kg of conductive adhesive solution with a solid content of 10%.

[0086] S2. Mixing and Dispersion: 28.8 kg of NCM811, 7.2 kg of LMFP, and 11 kg of NMP are fed into a dual planetary slurry mixer and pre-dispersed at 40℃, vacuum -0.098~-0.095 MPa, and linear velocity of 12 m / s for 1.5 h. Then, the linear velocity is increased to 20 m / s and dispersed for 3 h to obtain the positive electrode slurry.

[0087] The positive electrode slurry prepared in Comparative Example 1 has a solid content of 65%, a fineness of 20 μm, and a viscosity of 12000 mPa·s.

[0088] Comparative Example 2

[0089] A homogenization method for a composite cathode slurry, compared with Example 1, differs only in that steps S3 and S4 are swapped, with NCM dispersion performed first, followed by LMFP dispersion; the remaining operations and process conditions are the same as in Example 1. Details are as follows:

[0090] S1. Preparation of adhesive solution: 700g of PVDF and 9.0kg of NMP are added to a double planetary mixing machine for mixing. Then, 178g of SP and 122g of CNT are added in sequence. The dispersion linear velocity of the double planetary mixing machine is 14m / s. The mixture is stirred at 35℃ for 3h to obtain 10kg of conductive adhesive solution with a solid content of 10%.

[0091] S2. Basic kneading: Take 8 kg of conductive adhesive liquid, add 14.4 kg of NCM811 and 3.6 kg of LMFP to it, control the solid content to 72%, set the dispersion linear velocity of the double planetary mixing machine to 8 m / s, and disperse at 40℃ for 1.5 h.

[0092] S3, NCM dispersion: 14.4 kg of NCM811 was added to the S3 system, the dispersion linear velocity of the double planetary mixer was reduced to 12 m / s, and the mixture was dispersed at 40℃ for 30 min.

[0093] S4, LMFP dispersion: Add 3.6 kg of LMFP to the S2 system, increase the dispersion linear velocity of the double planetary mixer to 14 m / s, and disperse at 40℃ for 30 min;

[0094] S5. Final dispersion: Add the remaining conductive adhesive and 11 kg of NMP to the S4 system, set the dispersion linear velocity of the dual planetary slurry mixer to 12 m / s, and pre-disperse at 40℃ for 30 min; then increase the dispersion linear velocity to 20 m / s, and disperse at 40℃ and vacuum -0.098~-0.095 MPa for 1.5 h to obtain the positive electrode slurry.

[0095] The positive electrode slurry prepared in Comparative Example 2 has a solid content of 65%, a fineness of 16 μm, and a viscosity of 9120 mPa·s.

[0096] Detection example

[0097] The positive electrode slurries prepared in Examples 1-3 and Comparative Examples 1-2 were coated onto the current collector, dried, rolled, and slit to obtain positive electrode sheets; the positive electrode sheets were used to assemble lithium-ion batteries and electrochemical performance was tested.

[0098] I. Lithium-ion Battery Assembly

[0099] Positive electrode sheet (120 μm thick): The positive electrode slurry prepared in the examples and comparative examples was coated on carbon-coated aluminum foil, dried, rolled, and cut to obtain the positive electrode sheet;

[0100] Negative electrode (500μm thick): Lithium metal sheet is used;

[0101] Separator (16μm thick): Alumina ceramic coated polyethylene (PE) diaphragm;

[0102] Electrolyte: The electrolyte used is a 1 mol / L LiPF6-(EC:DMC:EMC=1:1:1) carbonate-based electrolyte, with the addition of 2% VC and 5% FEC;

[0103] Assembly of CR2032 button cell: The cells are assembled in an argon-protected glove box. The assembly sequence is as follows: negative electrode shell, stainless steel spring, gasket, negative electrode sheet, separator, electrolyte, positive electrode sheet, and positive electrode shell. After alignment and stacking, the cells are sealed using a sealing machine. The sealed button cells are left to stand at room temperature for 10–12 hours to allow the electrolyte to fully impregnate them before electrochemical performance testing.

[0104] II. Electrochemical Performance Testing

[0105] Electrochemical tests were conducted using a high-precision battery tester at a constant temperature of 25°C.

[0106] 1. Initial charge / discharge capacity: Charge at a constant current rate of 0.1C to the cutoff voltage of 4.25V. After reaching the upper voltage limit, switch to constant voltage charging until the charging current decays to 0.02C and the cutoff voltage is reached. Record the initial charge capacity. After resting for 10 minutes, discharge at a constant current rate of 0.1C to 2.75V and record the initial discharge capacity. Initial discharge specific capacity = initial discharge capacity / mass of active material.

[0107] 2. Cyclic Capacity Retention Test: A long-cycle test was conducted using a 0.5C charge and 0.5C discharge regime: The vehicle was charged at 0.5C constant current to 4.25V, then charged at constant voltage to 0.02C, and allowed to rest for 5 minutes; subsequently, it was discharged at 0.5C constant current to 2.75V, and allowed to rest for 5 minutes. This constituted one cycle. The capacity at the 3rd cycle was selected as the initial capacity, and then 150 cycles were performed, which was recorded as the final capacity. Capacity retention rate = final capacity / initial capacity × 100%.

[0108] 3. DCR Internal Resistance Test: The constant current pulse voltage drop method was used for testing. The assembled CR2032 button cells were uniformly calibrated to 50% SOC steady state and left to stand for 30 min to ensure the thermodynamic stability of the electrode interface. Then, a constant current pulse discharge of 1C was used for 10 s, and the voltage difference of the battery before and after the pulse discharge was recorded. The DC internal resistance of the battery was calculated according to the formula DCR=ΔU / I. Multiple batteries in each group of samples were tested in parallel, and the average value was taken after removing abnormal data.

[0109] III. Test Results

[0110] The test results are shown in Table 1 and Figure 3 As shown.

[0111] Table 1

[0112]

[0113] As shown in Table 1 and Figure 3 As shown, in Examples 1-3 using the segmented feeding process of the present invention, with the increase of LMFP doping ratio, the first discharge specific capacity of the composite cathode gradually decreases, the 150-cycle capacity retention gradually increases, and the DC internal resistance of DCR slightly increases. In Example 1, when the active material NCM811:LMFP = 8:2, compared with Comparative Example 1 (where the powder is fed in one go) and Comparative Example 2 (where the feeding order is reversed), Example 1 has a higher first-cycle specific capacity, better cycle stability, and lower DC internal resistance, confirming that the segmented feeding process of the present invention can improve the powder dispersion uniformity, construct a continuous conductive network, and simultaneously optimize the overall electrochemical performance of the composite cathode.

[0114] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention, based on the technical solution and inventive concept of the present invention, should be covered within the scope of protection of the present invention.

Claims

1. A method for homogenizing a composite positive electrode slurry, characterized in that, The semi-dry homogenization process includes the following steps: S1. Divide the solvent into two parts to obtain the first part of solvent and the second part of solvent; add the binder and conductive agent to the first part of solvent, stir and disperse to obtain the conductive adhesive; S2. Divide the conductive adhesive, ternary material, and lithium manganese iron phosphate into two portions each; mix the first portion of conductive adhesive, the first portion of ternary material, and the first portion of lithium manganese iron phosphate, knead and disperse to obtain the first kneaded material; S3. Add the second part of lithium manganese iron phosphate to the first kneading material, knead and disperse to obtain the second kneading material; S4. Add the second part of the ternary material to the second kneaded material, knead and disperse to obtain the third kneaded material; S5. Add the second part of conductive adhesive and the second part of solvent to the third kneading material, stir and disperse to obtain the positive electrode slurry.

2. The homogenization method according to claim 1, characterized in that, The solvent is selected from one or more of N-methylpyrrolidone, N-ethylpyrrolidone, propylene carbonate, dihydro-L-glucanone, and γ-valerol. The adhesive is selected from one or more of polyvinylidene fluoride, hydrogenated nitrile butadiene rubber, polyimide, and polyacrylonitrile; The conductive agent is selected from one or more of conductive carbon black, acetylene black, carbon nanotubes, and graphene. Preferably, the conductive adhesive has a solid content of 6-14% and a viscosity of 1000-3000 mPa·s.

3. The homogenization method according to claim 1 or 2, characterized in that, The mass ratio of the ternary material to lithium manganese iron phosphate is 6-9:1-4; the ternary material is NCM ternary material.

4. The homogenization method according to any one of claims 1-3, characterized in that, The solid content of the first kneaded material is 68-80%; Preferably, the positive electrode slurry has a solid content of 60-68%, a viscosity of 5000-8000 mPa·s, and a fineness of ≤15 μm.

5. The homogenization method according to any one of claims 1-4, characterized in that, The segmented control of linear velocity during homogenization process: In S1, the dispersion linear velocity is 10-15 m / s, and the temperature is controlled at ≤35℃; preferably, the dispersion time is 2-6 h. In S2, the dispersion linear velocity is 6-12 m / s, and the temperature is controlled at ≤40℃; preferably, the kneading and dispersion takes 60-90 min. In S3, the dispersion linear velocity is 10-18 m / s, and the temperature is controlled at ≤40℃; preferably, the kneading and dispersion is carried out for 20-40 min. In S4, the dispersion linear velocity is 10-18 m / s, and the temperature is controlled at ≤40℃; preferably, the kneading and dispersion is carried out for 20-40 min. In S5, the dispersion is first carried out at a medium speed with a dispersion linear velocity of 10-15 m / s, and then dispersed at a high speed with a dispersion linear velocity of 15-25 m / s. The temperature is controlled at ≤55℃, and degassing is carried out under a vacuum of -0.098 to -0.095 MPa. Preferably, the medium speed pre-dispersion is carried out for 20-40 min, and the high speed dispersion is carried out for 60-90 min. The dispersion linear velocity of S2 is less than that of S3 and S4.

6. The homogenization method according to any one of claims 1-5, characterized in that, S1-S5 use a dual planetary mixing machine for homogenization; The dispersion linear velocity of the dual planetary mixing machine is adjustable in the range of 6-25 m / s.

7. The homogenization method according to any one of claims 1-6, characterized in that, The first and second portions of solvent account for 30-70% and 70-30% of the total solvent mass, respectively. The first and second portions of conductive adhesive account for 40-80% and 20-60% of the total mass of the conductive adhesive, respectively. The first and second portions of the ternary material account for 40-60% and 40-60% of the total mass of the ternary material, respectively. The first and second portions of lithium manganese iron phosphate account for 40-60% and 40-60% of the total mass of lithium manganese iron phosphate, respectively.

8. The homogenization method according to any one of claims 1-7, characterized in that, The active material, conductive agent, and binder have mass fractions of 90-98%, 0.7-5%, and 1.3-5%, respectively. The active material includes ternary materials and lithium manganese iron phosphate, with a mass ratio of 6-9:1-4.

9. A positive electrode sheet for a lithium-ion battery, characterized in that, The positive electrode slurry prepared by the homogenization method described in any one of claims 1-8 is coated onto the current collector, and then dried, rolled, and slit to obtain the positive electrode sheet.

10. A lithium-ion battery, characterized in that, It includes the positive electrode sheet as described in claim 9.